A Retrospective Observational Cohort Study on the Expiration of Maxillary Cheek Teeth Infundibula in 217 Horses. (March 2023) - Dickey, Jason P.; Carmalt, James L.; Reiswig, Jeffrey D.
The determination of a horse's age by its dentition is a technique that has been employed by horse owners and professionals since at least 600 BC. While aging teeth based on incisor wear patterns is common, wear patterns in the cheek teeth may also be useful. As horses continue to live longer, we routinely examine horses into their 20's and 30's, and it is becoming more common to observe aging changes in the cheek teeth. To our knowledge, this study is the first to use easily obtained clinical observation of the expiration of cheek teeth infundibula to age horses of advanced ages (16 to 35 years). The results of this study indicate that the attrition of infundibula is likely due to the combined effects of eruption time, length of the tooth or infundibulum, forces placed on the tooth or infundibulum, and the presence of enamel or cemental hypoplasia. With additional prospective studies, the use of cheek tooth infundibular expiration may become a useful tool to determine the age of horses in the field.